Prevalence of Feline Leukemia Virus and Immunodeficiency in Feral Cats Treated in Two Operating Veterinary Clinics in Bogotá, Colombia (2023)
Feline leukemia virus (FeLV) and feline immunodeficiency virus (FIV) belong to the family of retroviruses that affect all cats in the world, including some feral cats. These retroviruses compromise the immune system, making the cats susceptible to secondary infections that can lead to serious and deadly diseases. Despite being diseases of high clinical importance, in Colombia the study on the prevalence of these diseases in stray felines has been scarce. Therefore, a prevalence study of feline leukemia and feline immunodeficiency was carried out in feral cats from the city of Bogotá, in periods from June 1, 2021, to June 20, 2022, and June 21, 2022, to April 2023. In the first period, 397 medical records were included, with a gender distribution of 37.27% females and 62.73% males. The second period had 298 medical records, with 37.91% females and 62.09% males. The prevalence of both diseases was higher in the first period, with 15.11% for FIV and 16.37% for FeLV, and in the second period it was 13.75% for FIV and 11.40% for FeLV. Additionally, the study revealed that males had a higher probability of infection in both diseases, according to the odds ratio. This study concluded that these diseases are present in a considerable proportion of the feral feline population, a condition that must be taken into account for the implementation of preventive measures.